THE EFFECT OF THE PROBLEM-BASED LEARNING MODEL ON LEARNING RESULTS MATHEMATICS STUDENT OF CLASS VIII - Rizka Elviany; Uus Kusdinar (Universitas Ahmad Dahlan, 2019)
A learning model that focuses on the teacher resulted in the students more passive in following the teaching and learning activities, especially math lessons, so that teaching and learning activities are still less satisfactory. This affects students' mathematics learning outcomes. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on grade VIII students' mathematics learning outcomes. This study's population is the students of class VIII Junior High School (SMP) Muhammadiyah Pleret 2016 school year consisting of 4 classes. The sampling technique used the purposive sampling technique and obtained class VIII D as experiment class and class VIII C as control class. The method of collecting data is done by the test method. The data analysis technique uses a prerequisite analysis test, including normality test, homogeneity test, and hypothesis tests. The research results obtained that (1) there are differences in learning outcomes between learning mathematics using Problem Based Learning model learning with Direct Learning model. This is based on the two-party hypothesis test obtained and with 5% significant level and degrees of freedom, respectively , and , which means , so H0 is accepted, and H1 is rejected. (2) Learning mathematics using Problem Based Learning model is more influential than the Direct Learning model toward the mathematics learning result of the VIII student of SMP Muhammadiyah Pleret of the academic year 2016/2017. This is indicated by a one-sided hypothesis test obtained and with a significant level of 5% and degrees of freedom, respectively and which means so H0 is accepted and H1 is rejected